Root-puncture-resistant asphalt waterproof coiled material and preparation method thereof
By combining copper-plated MXene composite material with SEBS-g-MAH modified asphalt in the asphalt waterproof roll, various problems in the use of existing asphalt waterproof rolls are solved, and the root puncture resistance, waterproof effect and self-monitoring function are improved, meeting the safety and stability requirements of modern buildings.
Patent Information
- Application Number
- CN202411832275.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing asphalt root-resistant waterproof coils have problems such as overlap gaps, complex construction, large energy consumption, and difficult to guarantee performance during use. Moreover, the mechanical properties and ductility of the copper tire base are poor, which cannot meet the safety and stability requirements of modern buildings.
The copper-plated MXene composite material is used as a reinforcement material and a root resistor, combined with SEBS-g-MAH modified asphalt cover material, and the copper-plated MXene tire-based self-monitoring waterproof coil is prepared through the electroless copper plating process to improve its root puncture resistance, waterproof effect and self-monitoring function.
It has achieved a coordinated improvement in the root puncture resistance, waterproofing effect and self-monitoring function of the coil material. It has high temperature stability, high tensile and tear strength, good conductivity, excellent self-monitoring ability, and reduced production costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of waterproof material preparation, and particularly relates to a root penetration resistant asphalt waterproof coiled material and a preparation method thereof. Background Art
[0002] In recent years, the development of green planting roofs has attracted more and more attention from all walks of life because green planting has good thermal insulation, heat insulation and energy-saving effects on buildings, and can effectively purify urban air and reduce the heat island effect. However, the traditional planting roof is inflexible and has a large load. The entire roof needs to be surface treated, which is not easy to operate, especially for the greening of old roofs. The green planting roof project consists of a number of comprehensive technologies such as planting, waterproofing, drainage, thermal insulation, etc. Among them, roof waterproofing technology is particularly important. Once leakage occurs, it will cause great economic losses. Root-piercing waterproof material refers to a high-efficiency waterproof material that inhibits the root system from further growing into the waterproof layer and avoids damaging the waterproof layer. The plant roots in the planting roof system have extremely strong penetrability. If the root-piercing waterproof material is not selected properly, it will be penetrated by the plant rhizomes, causing leakage in the building.
[0003] Asphalt root-penetration-resistant waterproofing membrane is one of the most widely used waterproofing materials at present, but it still has many limitations in the current use stage. First, due to its inherent size, asphalt root-penetration-resistant waterproofing membrane inevitably has overlapping gaps, which can easily become a defect of the green roof waterproofing system. Second, the construction of asphalt root-penetration-resistant waterproofing membranes mostly adopts hot-melt technology, which has many disadvantages such as complex construction, high energy consumption and difficult performance guarantee. Third, the copper base of asphalt root-penetration-resistant waterproofing membranes is mainly copper foil, which has poor mechanical properties and ductility. At the same time, traditional building materials can no longer meet people's requirements for safety and stability, so new self-monitoring functional building materials with better performance have emerged. However, today's self-monitoring functional building materials have a single component, a small sensing range, and a low sensitivity coefficient, which limits their application in the health monitoring of civil engineering structures. Therefore, the study of new self-monitoring functional building materials can solve people's requirements for safety. It is the "personal doctor" of the building structure, which monitors the health of the building structure in real time and prevents it before it happens. At the same time, it also has a positive role in promoting the development of functional building materials. Summary of the invention
[0004] In response to the above-mentioned problems in the prior art, the present application proposes a root penetration resistant asphalt waterproofing membrane and a preparation method thereof, which can achieve synergistic improvement of the root penetration resistance, waterproofing effect and self-monitoring function of the membrane.
[0005] The technical solution of the present invention is:
[0006] A method for preparing a root penetration resistant asphalt waterproofing membrane comprises the following steps:
[0007] Preparing a copper-plated MXene composite material, wherein the copper-plated MXene composite material is a surface copper-plated material of Ti3C2-MXene;
[0008] Preparation of SEBS-g-MAH modified asphalt coating material;
[0009] The copper-plated MXene composite material is prepared into a copper-plated MXene felt, which is used as a coil base and unfolded on a coil production line. It is fully infiltrated with an asphalt impregnation material, and then coated with the SEBS-g-MAH modified asphalt coating material. A polyethylene film is then applied to the upper and lower surfaces. After cooling and dwelling, the temperature is reduced, and the felt is packaged into a roll to obtain the root penetration resistant asphalt waterproofing coil.
[0010] Preferably, the specific steps of preparing the copper-plated MXene composite material are:
[0011] Preparation of Ti3C2-Mxene materials;
[0012] Chemical copper plating on the surface of Ti3C2-Mxene material.
[0013] Preferably, the asphalt impregnated material is obtained by heating No. 70 road petroleum asphalt in a heating furnace to melt it and remove moisture.
[0014] Preferably, in the process of chemical copper plating on the surface of the Ti3C2-Mxene material, the copper plating solution used is a mixture of 30-50 g / L copper sulfate, 20-40 g / L sodium hypophosphite, 50-70 g / L sodium citrate, 40-60 g / L ammonium chloride and 2-6 mg / L thiourea.
[0015] Preferably, the pH value of the copper plating solution is 9-12.
[0016] Preferably, the specific steps of preparing the SEBS-g-MAH modified asphalt coating material are:
[0017] 60-80 parts of No. 200 asphalt are input into a mixing tank, heated to 190°C, fully stirred, added with 15-30 parts by weight of SEBS-g-MAH and 3-5 parts by weight of furfural extracted oil, and circulated through the colloid mill and the mixing tank for 1-3 hours at a stirring rate of 3000-4500rpm / min; after the SEBS-g-MAH is fully ground, 15-30 parts by weight of talcum powder are added and fully stirred to obtain a SEBS-g-MAH modified asphalt coating material at a stirring rate of 1500-2000rpm / min.
[0018] Preferably, in the process of chemical copper plating on the surface of the Ti3C2-Mxene material, the Ti3C2-Mxene material is first purified, dispersed, sensitized and activated before chemical copper plating.
[0019] Preferably, the SEBS-g-MAH is FG-1901 maleic anhydride SEBS.
[0020] Preferably, the Ti3C2-Mxene material is prepared using HCl-LiF solution and Ti3AlC2 precursor powder.
[0021] The root penetration resistant asphalt waterproofing coiled material obtained by the preparation method.
[0022] The beneficial effects of the present invention include:
[0023] (1) The present invention uses copper-plated MXene as a reinforcing material and a root barrier agent. Compared with asphalt root barrier waterproofing membranes with added chemical root barrier agents, it has high-temperature stability and can avoid the loss of root barrier effect due to high-temperature decomposition of asphalt during hot-melt welding. Compared with copper foil-based asphalt root barrier waterproofing membranes, copper-plated MXene-based asphalt root penetration resistant waterproofing membranes have higher tensile and tear strengths. In addition, the surface copper plating method greatly reduces the use of precious metal copper and saves production costs.
[0024] (2) The present invention adopts highly conductive MXene material as the reinforcement of the asphalt substrate and combines it with the chemical copper plating process to prepare a copper-plated MXene-based self-monitoring waterproof membrane, which can achieve a synergistic improvement in the membrane's resistance to root penetration, waterproof effect, and self-monitoring function.
[0025] (3) Maleic anhydride-treated SEBS-g-MAH has better dispersibility within the asphalt, which makes it more compatible with the asphalt matrix and further enhances the mechanical strength of the copper-coated MXene-based asphalt root penetration-resistant waterproof membrane.
[0026] (4) SEBS-g-MAH grafted with maleic anhydride has both polar aldehyde groups and olefin non-polar segments, which can achieve a perfect combination of strength and toughness through chemical bonding with the -OH and =O groups on the surface of MXene, forming a suitable SEBS-g-MAH / asphalt / MXene polymer network inside the asphalt, thereby improving the various properties of the copper-plated MXene-based asphalt waterproof membrane, such as ductility, softening point, and bonding strength with the concrete interface. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with specific embodiments.
[0028] The present invention uses HCl-LiF solution and Ti3AlC2 precursor powder to prepare Ti3C2-MXene. In order to further improve the conductive performance of Ti3C2-MXene, the MXene composite conductive material is placed in a purified solution to remove impurities, neutralized, placed in a sensitizing solution for sensitization, repeatedly rinsed with clean water, and activated in an activation solution at the same time. The pH value of the copper plating solution is adjusted with ammonia water, and copper is plated in the copper plating solution. The asphalt impregnation material is prepared with No. 70 petroleum asphalt, and the SEBS-g-MAH modified asphalt coating material is prepared with No. 200 asphalt, SEBS-g-MAH, furfural extracted oil and talcum powder; the copper-plated MXene felt prepared from the copper-plated MXene composite conductive material is used as a coil base and unfolded on a coil production line, fully infiltrated with an asphalt impregnation material, coated with a SEBS-g-MAH modified asphalt coating material, and then a polyethylene film isolation material is applied on the surface, cooled and stopped, cooled, and packaged into a roll to obtain a copper-plated MXene base self-monitoring root-piercing resistant asphalt waterproof coil.
[0029] Example 1
[0030] This embodiment provides a method for preparing a root penetration resistant asphalt waterproofing membrane, comprising the following steps:
[0031] Step S101, preparing a copper-plated MXene composite material, wherein the copper-plated MXene composite material is a surface copper-plated material of Ti3C2-Mxene.
[0032] Among them, the preparation method of Ti3C2-MXene is as follows:
[0033] 1) At room temperature, 120 ml of 9 M HCl solution was slowly poured into a polytetrafluoroethylene beaker, and then 8.0 g of LiF was slowly added under magnetic stirring at 450 rpm. After stirring at a constant speed for 20 min to form a homogeneous system, 8.0 g of Ti3AlC2 precursor powder was slowly added in sequence and stirred at a constant speed for 15 min.
[0034] 2) Place the mixture in a constant temperature water bath (equipped with a magnetic stirrer) at 45°C and 500 rpm for a continuous reaction of 45 to 48 hours. After the reaction, wash and centrifuge the mixed solution with 1M LiCl, 1M HCl and deionized water (DI) in sequence, wherein the centrifugation is set at 5000 rpm for 10 minutes. Repeat the washing and centrifugation several times until the pH value of the supernatant is ≥6.5.
[0035] 3) The obtained product is placed in a vacuum freeze drying oven and dried for 72 hours to obtain the product Ti3C2-MXene. After the Ti3C2-MXene is prepared, chemical copper is plated on the surface of the Ti3C2-MXene. The specific steps are as follows:
[0036] 1) Purification treatment: Ti3C2-MXene was added to the purified solution, and after ultrasonication at room temperature for 30 min, it was placed in an 80 °C water bath for purification for 5 h.
[0037] The purified solution is a mixture of concentrated nitric acid and concentrated sulfuric acid (mass ratio 1:3).
[0038] 2) Dispersion treatment: The MXene material purified in step 1) was placed in deionized water and ultrasonically dispersed in a 45°C water bath for 90 min, and the cationic surfactant hexadecyltrimethylammonium bromide (CTAB) was added to further disperse the MXenes.
[0039] 3) Sensitization treatment: Place the MXene dispersed in step 2) in a sensitizing solution and sensitize it in a 50°C water bath for 60 minutes, and rinse it repeatedly with clean water.
[0040] The sensitizing solution is a mixture of 10 g / L stannous chloride and 40 ml / L hydrochloric acid.
[0041] 4) Activation treatment: The MXene sensitized in step 3) is placed in an activation solution and activated at 25°C for 45 minutes. After standing, it is centrifuged and washed with DI until neutral.
[0042] The activation solution is a mixture of 0.5 g / L palladium chloride and 20 ml / L hydrochloric acid, wherein the mass percentage concentration of the hydrochloric acid is 38%;
[0043] 5) Chemical copper plating treatment:
[0044] The pH value of the copper plating solution is adjusted to 10-12 with ammonia water, and the MXene activated in step 4) is placed in the copper plating solution for chemical copper plating. The chemical copper plating reaction temperature is 40-80°C, the copper plating time is 25-60min, and the copper-plated MXene composite material is obtained after centrifugal drying.
[0045] The copper plating solution is a mixture of 30 g / L copper sulfate, 30 g / L sodium hypophosphite, 65 g / L sodium citrate, 50 g / L ammonium chloride and 4 mg / L thiourea.
[0046] Step S102, preparing SEBS-g-MAH modified asphalt coating material.
[0047] The specific steps are as follows: 80 parts of No. 200 asphalt are pumped into a metering modified stirring tank, heated to 190°C and fully mixed for a certain period of time, 15 parts of SEBS-g-MAH and 3 parts of furfural extracted oil are added, and circulated through a colloid mill and a stirring tank for 1 hour at a stirring rate of 3000-4500rpm / min; after SEBS-g-MAH is fully ground, 20 parts of talcum powder are added and fully stirred to obtain a SEBS-g-MAH modified asphalt coating material at a stirring rate of 1500-2000rpm / min.
[0048] Step S103, prepare the copper-plated MXene composite material into copper-plated MXene felt, use the copper-plated MXene felt as a coil base and unfold it on a coil production line, fully infiltrate it with the asphalt impregnation material, then coat it with the SEBS-g-MAH modified asphalt coating material, and then apply a polyethylene film on the upper and lower surfaces, cool and dwell, reduce the temperature, and package it into a roll to obtain the root penetration resistant asphalt waterproof coiled material.
[0049] The asphalt impregnated material is obtained by heating No. 70 road petroleum asphalt to 100° C. in a heating furnace to melt it and remove moisture.
[0050] Example 2
[0051] This embodiment is substantially the same as Embodiment 1, except that:
[0052] In step (2) chemical copper plating on the surface of the MXene composite material, in step ④, the pH value of the copper plating solution is adjusted to 10 with ammonia water, and the MXene activated in step ③ is placed in the copper plating solution for copper plating at 80° C. for 20 minutes, and the copper-plated MXene is obtained after drying.
[0053] The copper plating solution is a mixture of 50 g / L copper sulfate, 25 g / L sodium hypophosphite, 50 g / L sodium citrate, 60 g / L ammonium chloride and 3 mg / L thiourea.
[0054] Example 3
[0055] This embodiment is substantially the same as Embodiment 1, except that:
[0056] In step (2) chemical copper plating on the surface of the MXene composite material, in step ④, the pH value of the copper plating solution is adjusted to 11 with ammonia water, and the MXene activated in step ③ is placed in the copper plating solution for copper plating at 85° C. for 25 minutes, and the copper-plated MXene is obtained after drying.
[0057] The copper plating solution is a mixture of 45 g / L copper sulfate, 45 g / L sodium hypophosphite, 70 g / L sodium citrate, 40 g / L ammonium chloride and 5 mg / L thiourea.
[0058] Example 4
[0059] This embodiment is substantially the same as Embodiment 1, except that:
[0060] In step (2) chemical copper plating on the surface of the MXene composite material, in step ④, the pH value of the copper plating solution is adjusted to 10 with ammonia water, and the MXene activated in step ③ is placed in the copper plating solution for copper plating, and the copper plating is performed at 90° C. for 10 minutes, and the copper-plated MXene is obtained after drying.
[0061] The copper plating solution is a mixture of 35 g / L copper sulfate, 40 g / L sodium hypophosphite, 55 g / L sodium citrate, 55 g / L ammonium chloride and 2 mg / L thiourea.
[0062] Example 5
[0063] This embodiment is substantially the same as Embodiment 1, except that:
[0064] In the process of chemical copper plating on the surface of the MXene composite material in step (2), the pH value of the copper plating solution is adjusted to 9 with ammonia water in step ④, and the MXene activated in step ③ is placed in the copper plating solution for copper plating at 80° C. for 30 minutes, and the copper-plated MXene is obtained after drying.
[0065] The copper plating solution is a mixture of 45 g / L copper sulfate, 35 g / L sodium hypophosphite, 60 g / L sodium citrate, 55 g / L ammonium chloride and 6 mg / L thiourea.
[0066] Comparative Example 1
[0067] (1) Preparation of Ti3C2-MXene
[0068] ① Pour 25 ml of 40% hydrofluoric acid solution into a three-necked flask, then slowly add 1.5 g of Ti3AlC2 precursor powder and let stand in an ice bath for 10 min.
[0069] ② Stir the mixture in a magnetic stirrer at 50°C and 800 rad / min for 30 hours. Centrifuge the mixture in a high-speed centrifuge at 3000 rad / min for 10 minutes.
[0070] ③ Pour out the supernatant, wash the reaction solution alternately with deionized water and anhydrous ethanol and filter, repeat the washing several times until the pH value of the supernatant is 5-6.
[0071] ④ The obtained product was placed in a vacuum drying oven and dried at 50°C to obtain the product Ti3C2-MXene.
[0072] (2) Chemical copper plating on MXene composite surface
[0073] ① Place the MXene composite material in a degreasing liquid and degrease at 40°C for 30 minutes, and place the treated MXene in 10wt% dilute sulfuric acid to neutralize the alkali solution on the surface.
[0074] The degreasing liquid is a mixture of 60 g / L sodium hydroxide, 30 g / L sodium carbonate and 15 g / L sodium phosphate;
[0075] ② Place the Ag / MXene that has been degreased and neutralized in step ① in the sensitizing solution and sensitize it at 25°C for 10 minutes, and rinse it repeatedly with clean water.
[0076] The sensitizing solution is a mixture of 10 g / L stannous chloride and 40 ml / L hydrochloric acid; the hydrochloric acid concentration is 38%;
[0077] ③ Place the MXene sensitized in step ② in the activation solution and activate it at 25℃ for 10 min to remove the Pd 2+ The ions were converted into metallic Pd particles, and then placed in 10 g / L sodium hypophosphite for 10 min to reduce the surface Pd 2+ .
[0078] The activation solution is a mixture of 0.5 g / L palladium chloride and 20 ml / L hydrochloric acid, wherein the concentration of the hydrochloric acid is 38%.
[0079] ④ Use ammonia water to adjust the pH value of the copper plating solution to 10, place the MXene activated in step ③ in the copper plating solution for copper plating, the copper plating temperature is 90°C, the copper plating time is 10 minutes, and after drying, the copper-plated MXene composite material is obtained.
[0080] The copper plating solution is a mixture of 35 g / L copper sulfate, 40 g / L sodium hypophosphite, 55 g / L sodium citrate, 55 g / L ammonium chloride and 2 mg / L thiourea.
[0081] (3) Preparation of self-monitoring root penetration resistant waterproof membrane prepared by copper-plated MXene:
[0082] ① Place No. 70 road petroleum asphalt in a heating furnace and heat it to 100°C to melt it and remove moisture to obtain asphalt impregnated material;
[0083] ② 80 parts of No. 200 asphalt are pumped into the metering modification mixing tank, heated to 190°C and fully mixed for a certain period of time, 10 parts of SEBS-g-MAH and 3 parts of furfural extracted oil are added and circulated through the colloid mill and the mixing tank for 1 hour, after SEBS-g-MAH is fully ground, 20 parts of talcum powder are added and fully stirred to obtain SEBS-g-MAH modified asphalt coating material;
[0084] ③ The copper-plated MXene felt prepared from the copper-plated MXene composite material obtained in step (2)④ is used as a coil base, unfolded on a coil production line, fully infiltrated with the asphalt impregnated material obtained in step (3)①, and then coated with the SEBS-g-MAH modified asphalt coating material obtained in step (3)②, and then a polyethylene film for isolation is applied to the upper and lower surfaces of the coil base, and after cooling and dwelling, the temperature is reduced, and the coil is packaged into a roll to obtain a copper-plated MXene base self-monitoring root penetration resistant asphalt waterproofing coil.
[0085] Comparative Example 2
[0086] Same as Comparative Example 1, except that
[0087] In the preparation process of the copper-plated MXene self-monitoring root penetration resistant waterproof membrane in step (3), 80 parts of No. 200 asphalt are pumped into the metering modified stirring tank in ②, heated to 190°C and fully mixed for a certain time, 20 parts of SEBS-g-MAH and 3 parts of furfural extracted oil are added and circulated through the colloid mill and the stirring tank for 1 hour, and the other parameters remain unchanged.
[0088] Comparative Example 3
[0089] Same as Comparative Example 1, except that
[0090] In the preparation process of the copper-plated MXene self-monitoring root penetration resistant waterproof membrane in step (3), 80 parts of No. 200 asphalt are pumped into the metering modified stirring tank in ②, heated to 190°C and fully mixed for a certain time, 15 parts of ordinary SEBS that has not been treated with maleic anhydride and 3 parts of furfural extracted oil are added and circulated through the colloid mill and the stirring tank for 1 hour, and the other parameters remain unchanged.
[0091] Comparative Example 4
[0092] Same as Comparative Example 1, except that
[0093] In the preparation process of the copper-plated MXene self-monitoring root penetration resistant waterproof membrane in step (3), 80 parts of No. 200 asphalt are pumped into the metering modified stirring tank in ②, heated to 190°C and fully mixed for a certain time, 15 parts of SBS and 3 parts of furfural are added to extract the oil and circulate it through the colloid mill and the stirring tank for 1 hour, and the other parameters remain unchanged.
[0094] The applicant conducted performance tests on the self-monitoring root penetration resistant asphalt waterproof membrane prepared with copper-plated MXene obtained in each embodiment according to national standards GB / T 28.8-2007, GB / T328.18-2007, GB / T328.10-2007 and industry standard JC / T 1075-2008.
[0095] The resistivity of the copper-coated MXene-based self-monitoring root penetration-resistant asphalt waterproof membrane was measured using a four-probe resistance tester (test current 1 mA, sample diameter 5 cm).
[0096] The test results of Examples 1-5 and Comparative Examples 1-4 are shown in the table below.
[0097]
[0098]
[0099] It can be seen from the table that the self-monitoring root penetration resistant asphalt waterproof membrane prepared in the embodiment of the present invention has high tensile strength and good tear strength, good impermeability and root penetration resistance, low resistivity (good electrical conductivity), and excellent self-monitoring ability.
[0100] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a root penetration resistant asphalt waterproofing membrane, characterized in that: The steps include: Preparing a copper-plated MXene composite material, wherein the copper-plated MXene composite material is a surface copper-plated material of Ti3C2-MXene; Preparation of SEBS-g-MAH modified asphalt coating material; The copper-plated MXene composite material is prepared into a copper-plated MXene felt, which is used as a coil base and unfolded on a coil production line. It is fully infiltrated with an asphalt impregnation material, and then coated with the SEBS-g-MAH modified asphalt coating material. A polyethylene film is then applied to the upper and lower surfaces. After cooling and dwelling, the temperature is reduced, and the felt is packaged into a roll to obtain the root penetration resistant asphalt waterproofing coil.
2. The preparation method according to claim 1, characterized in that The specific steps of preparing the copper-plated MXene composite material are: Preparation of Ti3C2-Mxene materials; Chemical copper plating on the surface of Ti3C2-Mxene material.
3. The preparation method according to claim 1, characterized in that: The asphalt impregnated material is obtained by heating No. 70 road petroleum asphalt in a heating furnace to melt it and remove moisture.
4. The preparation method according to claim 1, characterized in that: In the process of chemical copper plating on the surface of the Ti3C2-Mxene material, the copper plating solution used is a mixture of 30-50 g / L copper sulfate, 20-40 g / L sodium hypophosphite, 50-70 g / L sodium citrate, 40-60 g / L ammonium chloride and 2-6 mg / L thiourea.
5. The preparation method according to claim 1, characterized in that: The pH value of the copper plating solution is 9-12.
6. The preparation method according to claim 1, characterized in that: The specific steps of preparing the SEBS-g-MAH modified asphalt coating material are: 60-80 parts of No. 200 asphalt are input into a mixing tank, heated to 190°C, fully stirred, added with 15-30 parts by weight of SEBS-g-MAH and 3-5 parts by weight of furfural extracted oil, and circulated through the colloid mill and the mixing tank for 1-3 hours at a stirring rate of 3000-4500rpm / min; after the SEBS-g-MAH is fully ground, 15-30 parts by weight of talcum powder are added and fully stirred to obtain a SEBS-g-MAH modified asphalt coating material at a stirring rate of 1500-2000rpm / min.
7. The preparation method according to claim 1 or 2, characterized in that: In the process of chemical copper plating on the surface of Ti3C2-Mxene material, the Ti3C2-Mxene material is first purified, dispersed, sensitized and activated before chemical copper plating.
8. The preparation method according to claim 1, characterized in that: The SEBS-g-MAH is FG-1901 maleic anhydride SEBS.
9. The preparation method according to claim 1, characterized in that: The Ti3C2-Mxene material is prepared using HCl-LiF solution and Ti3AlC2 precursor powder.
10. The root penetration resistant asphalt waterproofing membrane obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Copper plating glass fiber pad asphalt root-puncture-resistant waterproof coil
CN109440486A
Anti-aging polymer modified asphalt prepared from MXene and preparation method thereof
CN114806195A
Chemical plating product, chemical plating method and application
CN117004934A
Cote 2 / mxene composite material and preparation method therefor
WO2022032743A1
Cited By
Fast-curing waterproof polyurea as well as preparation method and application thereof
CN120699226A